A kind of impact-resistant protective film and preparation method thereof

By using a combined structure of PET light release film layer, OCA optical glue layer, optical grade PET film layer, silicone layer and PET releasing film on the electronic product screen, combined with modified silica and photoinitiator, the current solution is solved There is a problem that the protective film is easily damaged during impact, achieving efficient impact resistance and fit integrity.

CN118006232BActive Publication Date: 2024-12-27深圳市精恒光电科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410113579.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2024-12-27
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

Existing electronic product screen protectors are prone to damage when impacted, and cannot effectively prevent the potential risks of glass screens.

Method used

The impact protection film consisting of PET light release film layer, OCA optical glue layer, optical grade PET film layer, silicone layer and PET releasing film are adopted. Through the synergy of materials such as modified silica and photoinitiator, it is used to carry out the impact protection film composed of PET light release film layer, OCA optical glue layer, optical grade PET film layer, silicon gel layer and PET releasing film. Enhance impact resistance and adhesion.

Benefits of technology

Achieve impact resistance without breaking when impacted by using 130 grams of steel balls at a high distance of two meters, maintain the light transmittance and color clarity of the screen, and quickly eliminate bubbles through the adsorption force of the silicone layer to ensure the integrity of the fit and optical transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004684272370000081
    Figure BDA0004684272370000081
Patent Text Reader

Abstract

The present application relates to the technical field of protective films, and in particular to an impact-resistant protective film and a preparation method thereof. An impact-resistant protective film comprises: a PET light release film layer, an OCA optical adhesive layer, an optical-grade PET film layer, a silicone layer and a PET heavy release film, wherein the PET light release film layer, the OCA optical adhesive layer, the optical-grade PET film layer, the silicone layer and the PET heavy release film are sequentially bonded and connected from top to bottom, wherein the OCA optical adhesive layer, by mass, comprises the following preparation raw materials: n-propyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, diluent, glycidyl acrylate, modified silica, photoinitiator, cross-linking agent and antioxidant; the thickness of the OCA optical adhesive layer is 190‑210 μm. The impact-resistant protective film of the present application has beneficial technical effects such as high light transmittance, good impact resistance, strong adhesion, excellent installation effect and strong durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of protective films, and in particular to an anti-impact protective film and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology, electronic products such as mobile phones and tablets can be seen everywhere in life. Most of these electronic devices use touch screen panels for human-computer interaction as a medium for information collection and identification.

[0003] Touch screen panels generally use glass screens. In order to enjoy the convenience brought by electronic products while preventing potential risks brought by the glass screen itself, it is necessary to attach a protective film to the glass screen of the electronic product. However, the existing screen protective films of current electronic products are easily damaged by impact, so there is room for improvement. Summary of the invention

[0004] The purpose of this application is to provide an anti-impact protective film and a preparation method thereof in view of the deficiencies of the current technology.

[0005] In a first aspect, the present application provides an anti-impact protective film, which adopts the following technical solution:

[0006] An anti-impact protective film comprises: a PET light release film layer, an OCA optical adhesive layer, an optical-grade PET film layer, a silicone layer and a PET heavy release film, wherein the PET light release film layer, the OCA optical adhesive layer, the optical-grade PET film layer, the silicone layer and the PET heavy release film are sequentially bonded and connected from top to bottom, wherein the OCA optical adhesive layer comprises the following preparation raw materials by mass: 20-25 parts of n-propyl acrylate, 25-30 parts of isobornyl methacrylate, 2-4 parts of hydroxyethyl acrylate, 30-35 parts of diluent, 2-3 parts of glycidyl acrylate, 5-7 parts of modified silica, 0.5-1 parts of photoinitiator, 0.5-1 parts of cross-linking agent and 0.8-1.2 parts of antioxidant; the thickness of the OCA optical adhesive layer is 190-210 μm.

[0007] By adopting the above technical scheme, the optical-grade PET film layer: This layer has good light transmittance and can maintain the original clarity and color reproduction of the screen. OCA optical adhesive layer: The OCA optical adhesive layer is an optical adhesive that plays a bonding role between the PET light release film layer and the optical-grade PET film layer, which can effectively eliminate bubbles and improve adhesion. In addition, the preparation raw materials of the OCA optical adhesive layer contain modified silica, which enhances the interface performance between the optical adhesive layer and the PET film and improves the impact resistance. Silicone layer: In actual use, the silicone layer has good adsorption force, can firmly adhere the protective film to the surface of the screen, and can quickly eliminate bubbles to ensure the integrity and optical transparency of the fit. The synergistic effect of the above layers makes the anti-impact protective film have excellent impact resistance. The OCA optical adhesive layer can absorb and disperse the impact force and reduce the impact on the screen; the optical-grade PET film layer maintains the clarity and color reproduction of the screen; and the modified silica enhances the interface performance of the optical adhesive layer and improves the impact resistance of the entire structure. Therefore, each layer plays an important role in the anti-impact protective film, working together to provide anti-impact effect and adhesion.

[0008] Preferably, the thickness of the PET light release film layer is 47-53 μm; the thickness of the PET heavy release film layer is 72-78 μm; the thickness of the optical-grade PET film layer is 72-78 μm, and its light transmittance is 98%.

[0009] Preferably, the thickness of the silicone layer is 42-48 μm; the peeling force of the silicone layer is ≤6 g / inch at 300 mm / min and 180° according to JIS Z0237 standard; and the adhesion between the silicone layer and the glass is 3-6 g / inch.

[0010] By adopting the above technical solution, the silicone layer has good adsorption and exhaust performance. It can firmly adhere to the screen glass and quickly remove bubbles, making the fit complete and optically transparent. The adhesion between the silicone layer and the glass is 3-6g / inch, and the peeling force is ≤6g / inch, which can well meet the performance requirements.

[0011] Preferably, the method for preparing the modified silicon dioxide comprises the following steps:

[0012] S41, ultrasonically dispersing 10 g of nano-silica in an ethanol aqueous solution of 50 g of ethanol and 10 g of water, adding 4 g of γ-aminopropyltriethoxysilane, setting the system temperature to 75° C., stirring for 6-10 h, and after the reaction is completed, centrifuging the solid sample, washing, and drying to obtain γ-aminopropyltriethoxysilane-modified silica;

[0013] S42. Add the obtained γ-aminopropyltriethoxysilane modified silica to 30 g of tetrahydrofuran, disperse by ultrasonic, add 1.2 g of 2,6-di-tert-butylphenol and 2.5 g of potassium carbonate, mix well, raise the system temperature to 75°C, react for 7-12 hours, centrifuge the product to separate the solid sample, wash the solid sample with deionized water to neutrality, and finally dry in vacuum to obtain modified silica.

[0014] Preferably, the average particle size of the nano-silicon dioxide is 30 nm.

[0015] By adopting the above technical scheme, for the preparation of modified silica, the nano-silica modified by γ-aminopropyltriethoxysilane is reacted with 2,6-di-tert-butylphenol to form modified silica. This modified silica can enhance the lipophilicity and functionality of nano-silica, improve the interface performance with OCA optical adhesive, and further enhance the impact resistance of the protective film. The addition of modified silica can enhance the interface performance of the OCA optical adhesive layer, improve the agglomeration of nano-silica, form physical cross-linking points with nano-silica as the core, and enhance the impact resistance of OCA optical adhesive.

[0016] Preferably, the diluent is one of hydroxyethyl methacrylate, pentaerythritol rosin ester and isooctyl acrylate.

[0017] Preferably, the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5.

[0018] By adopting the above technical scheme, the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5. The photoinitiator is a photosensitizer, which can absorb light energy and convert it into chemical energy through its light absorption effect, thereby initiating a chemical reaction of the active substances around the photoinitiator. In the preparation process of the OCA optical adhesive layer, the photoinitiator can undergo a photochemical reaction by being excited by light, triggering the cross-linking reaction of other components, thereby promoting the curing and cross-linking of the optical adhesive layer. 2-Hydroxy-2-methyl-1-phenylpropanone is a photoactive compound, which can be used as the main component of the photoinitiator, and participates in the cross-linking reaction of the OCA optical adhesive through the free radical or ion reaction generated by light initiation. Its presence can increase the cross-linking density of the OCA optical adhesive layer and enhance the tensile strength and flexibility of the adhesive layer. 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and 4-methoxyacetophenone are used as auxiliary photoinitiators, which can react with 2-hydroxy-2-methyl-1-phenylacetone to initiate a photoinitiator reaction, further enhancing the sensitization effect of the photoinitiator and improving the reaction rate and crosslinking effect of the OCA optical adhesive layer. Through the action and synergistic effect of the photoinitiator, the curing and crosslinking of the OCA optical adhesive layer can be accelerated, the flexibility of the OCA optical adhesive layer can be improved, and the impact resistance of the entire anti-impact protective film can be further improved.

[0019] Preferably, the cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2.

[0020] By adopting the above technical scheme, the crosslinking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2. The crosslinking agent is a chemical substance used to promote the crosslinking reaction of the OCA optical adhesive layer. It can connect the polymer chains in the OCA optical adhesive layer to form a crosslinked network structure by initiating or catalyzing the crosslinking reaction. The crosslinked OCA optical adhesive layer has higher tensile strength and flexibility, thereby enhancing the impact resistance of the entire anti-impact protective film. Triphenyl glycidyl ether methane is a commonly used crosslinking agent, which can react with the hydroxyl-containing polymer in the OCA optical adhesive layer to form a chemical bond and promote the crosslinking reaction. Its presence can improve the crosslinking density and heat resistance of the OCA optical adhesive layer and enhance the tensile strength of the adhesive layer. Vinyl cyclohexene diepoxide is a compound with an epoxy group, which can react with the hydroxyl-containing polymer in the OCA optical adhesive layer to undergo an epoxy ring-opening polymerization reaction to form a crosslinked structure. Its addition can further improve the crosslinking degree and mechanical properties of the OCA optical adhesive layer, making it more impact-resistant. Through the action and synergistic effect of the cross-linking agent, the cross-linking performance and impact resistance of the OCA optical adhesive layer can be effectively enhanced, the flexibility of the adhesive layer can be improved, and then the impact resistance of the entire anti-impact protective film can be improved.

[0021] Preferably, the antioxidant is at least one of tert-butylhydroquinone, hexaethylphosphorotriamide and thiophosphoryl disulfide.

[0022] In a second aspect, the present application provides a method for preparing an impact-resistant protective film, which adopts the following technical solution:

[0023] As a general technical concept, the present application also provides a method for preparing the above-mentioned impact-resistant protective film, comprising the following steps: S101, stirring and mixing n-propyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, a diluent, glycidyl acrylate, modified silica, a photoinitiator, a crosslinking agent and an antioxidant to obtain an OCA optical adhesive for standby use;

[0024] S102, coating the surface of the optical-grade PET film layer with silica gel, and after heat curing, forming a silica gel layer, and then attaching the PET heavy release film light film layer to the silica gel layer, and performing electrostatic treatment on the side of the optical-grade PET film layer that is not coated with silica gel;

[0025] S103, coating the OCA optical adhesive on the surface of the optical grade PET film layer after electrostatic treatment, and curing it with ultraviolet light for 25-35 minutes to form an OCA optical adhesive layer, and finally attaching the PET light release film layer to the OCA optical adhesive layer to obtain an impact-resistant protective film, wherein the ultraviolet curing conditions are a wavelength of 360nm and an energy of 1000-2000mj / cm 2 .

[0026] In summary, the beneficial technical effects of this application are:

[0027] 1. Good light transmittance: The anti-impact protective film has good light transmittance, which reaches more than 92%, and can maintain the clarity of the screen display effect.

[0028] 2. Excellent anti-impact performance: The glass with the anti-impact protective film can withstand the impact test of a 130-gram steel ball at a distance of two meters without breaking, showing excellent anti-impact ability and effectively protecting the screen.

[0029] 3. Function of the silicone layer: The silicone layer has adsorption capacity for the screen glass, can quickly remove bubbles, and during the bonding process can ensure that the exhaust on the glass surface is clean, without snowflakes or white spots, thereby improving the quality and appearance of the installation.

[0030] 4. Nano-silica modification: Through the modification of nano-silica, its surface is rich in amino groups, which has stronger interfacial properties with the OCA optical adhesive matrix, effectively improves the agglomeration of nano-silica, forms physical cross-linking points, enhances the impact resistance of the OCA optical adhesive layer, and thus improves the impact resistance of the entire anti-impact protective film. DETAILED DESCRIPTION

[0031] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0032] Preparation Example 1 Preparation of modified silicon dioxide

[0033] The preparation method of modified silicon dioxide comprises the following steps:

[0034] S41, ultrasonically dispersing 10 g of nano-silica with an average particle size of 30 nm in an ethanol aqueous solution of 50 g of ethanol and 10 g of water, adding 4 g of γ-aminopropyltriethoxysilane, setting the system temperature to 75° C., stirring for 8 h, and after the reaction is completed, centrifuging the solid sample, washing, and drying to obtain γ-aminopropyltriethoxysilane-modified silica;

[0035] S42. Add the obtained γ-aminopropyltriethoxysilane modified silica to 30 g of tetrahydrofuran, disperse by ultrasonication, add 1.2 g of 2,6-di-tert-butylphenol and 2.5 g of potassium carbonate, mix well, raise the system temperature to 75°C, react for 9 hours, centrifuge the product to separate the solid sample, wash the solid sample with deionized water to neutrality, and finally dry in vacuum to obtain modified silica.

[0036] Example 1

[0037] An impact-resistant protective film comprises: a PET light release film layer, an OCA optical adhesive layer, an optical-grade PET film layer, a silicone layer and a PET heavy release film, wherein the PET light release film layer, the OCA optical adhesive layer, the optical-grade PET film layer, the silicone layer and the PET heavy release film are sequentially bonded and connected from top to bottom, wherein the thickness of the OCA optical adhesive layer is 190 μm, the thickness of the PET light release film layer is 53 μm; the thickness of the PET heavy release film layer is 72 μm; the thickness of the optical-grade PET film layer is 72 μm, and its light transmittance is 98%; the thickness of the silicone layer is 42 μm; the peeling force of the silicone layer is 3 g / in under the conditions of 300 mm / min and 180° according to JIS Z0237 standard. ch; the adhesion between the silicone layer and the glass is 3g / inch, and the OCA optical adhesive layer includes the following preparation raw materials in parts by mass: 200g of n-propyl acrylate, 250g of isobornyl methacrylate, 20g of hydroxyethyl acrylate, 300g of hydroxyethyl methacrylate, 20g of glycidyl acrylate, 50g of modified silica, 5g of photoinitiator, 5g of cross-linking agent, and 8g of tert-butylhydroquinone; the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and 4-methoxyacetophenone in a mass ratio of 3:2:5, and the cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2.

[0038] The method for preparing the above-mentioned anti-impact protective film comprises the following steps:

[0039] S101, stirring and mixing n-propyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, glycidyl acrylate, modified silica, a photoinitiator, a crosslinking agent and tert-butylhydroquinone to obtain an OCA optical adhesive for standby use;

[0040] S102, coating the surface of the optical-grade PET film layer with silica gel, and after heat curing, forming a silica gel layer, and then attaching the PET heavy release film light film layer to the silica gel layer, and performing electrostatic treatment on the side of the optical-grade PET film layer that is not coated with silica gel;

[0041] S103, coating the OCA optical adhesive on the surface of the optical grade PET film layer after electrostatic treatment, and curing it with UV light for 25 minutes to form an OCA optical adhesive layer, and finally attaching the PET light release film layer to the OCA optical adhesive layer to obtain an impact-resistant protective film, wherein the UV curing conditions are a wavelength of 360nm and an energy of 2000mj / cm 2 .

[0042] Example 2

[0043] An impact-resistant protective film comprises: a PET light release film layer, an OCA optical adhesive layer, an optical-grade PET film layer, a silicone layer and a PET heavy release film, wherein the PET light release film layer, the OCA optical adhesive layer, the optical-grade PET film layer, the silicone layer and the PET heavy release film are sequentially bonded and connected from top to bottom, wherein: the thickness of the OCA optical adhesive layer is 210 μm, the thickness of the PET light release film layer is 53 μm; the thickness of the PET heavy release film layer is 78 μm; the thickness of the optical-grade PET film layer is 78 μm, and its light transmittance is 98%; the thickness of the silicone layer is 48 μm; the peeling force of the silicone layer is 6 g / inch at 300 mm / min and 180° according to JIS Z0237 standard. The adhesion between the silicone layer and the glass is 6g / inch. The OCA optical adhesive layer includes the following raw materials by mass: 250g of n-propyl acrylate, 300g of isobornyl methacrylate, 40g of hydroxyethyl acrylate, 350g of rosin pentaerythritol ester, 30g of glycidyl acrylate, 70g of modified silica, 10g of photoinitiator, 10g of cross-linking agent, and 12g of hexaethylphosphite; the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and 4-methoxyacetophenone in a mass ratio of 3:2:5, and the cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2.

[0044] The method for preparing the above-mentioned anti-impact protective film comprises the following steps:

[0045] S101, stirring and mixing n-propyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, pentaerythritol rosin, glycidyl acrylate, modified silica, a photoinitiator, a crosslinking agent and hexaethylphosphoramidite to obtain an OCA optical adhesive for standby use;

[0046] S102, coating the surface of the optical-grade PET film layer with silica gel, and after heat curing, forming a silica gel layer, and then attaching the PET heavy release film light film layer to the silica gel layer, and performing electrostatic treatment on the side of the optical-grade PET film layer that is not coated with silica gel;

[0047] S103, coating the OCA optical adhesive on the surface of the optical grade PET film layer after electrostatic treatment, and curing it with UV light for 35 minutes to form an OCA optical adhesive layer, and finally attaching the PET light release film layer to the OCA optical adhesive layer to obtain an impact-resistant protective film, wherein the UV curing conditions are a wavelength of 360nm and an energy of 1000mj / cm 2 .

[0048] Example 3

[0049] An impact-resistant protective film comprises: a PET light release film layer, an OCA optical adhesive layer, an optical-grade PET film layer, a silicone layer and a PET heavy release film, wherein the PET light release film layer, the OCA optical adhesive layer, the optical-grade PET film layer, the silicone layer and the PET heavy release film are sequentially bonded and connected from top to bottom, wherein the OCA optical adhesive layer has a thickness of 200 μm, the PET light release film layer has a thickness of 50 μm; the PET heavy release film layer has a thickness of 75 μm; the optical-grade PET film layer has a thickness of 75 μm, and its light transmittance is 98%; the silicone layer has a thickness of 45 μm; and the peeling force of the silicone layer is 5 g / inc at 300 mm / min and 180° according to JIS Z0237 standard. h; the adhesion between the silicone layer and the glass is 5g / inch, and the OCA optical adhesive layer includes the following preparation raw materials in parts by mass: 230g of n-propyl acrylate, 280g of isobornyl methacrylate, 30g of hydroxyethyl acrylate, 330g of isooctyl acrylate, 25g of glycidyl acrylate, 60g of modified silica, 8g of photoinitiator, 8g of cross-linking agent, and 10g of thiophosphoryl disulfide; the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5, and the cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2.

[0050] The method for preparing the above-mentioned anti-impact protective film comprises the following steps:

[0051] S101, stirring and mixing n-propyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, isooctyl acrylate, glycidyl acrylate, modified silica, a photoinitiator, a crosslinking agent and thiophosphoryl disulfide to obtain an OCA optical adhesive for standby use;

[0052] S102, coating the surface of the optical-grade PET film layer with silica gel, and after heat curing, forming a silica gel layer, and then attaching the PET heavy release film light film layer to the silica gel layer, and performing electrostatic treatment on the side of the optical-grade PET film layer that is not coated with silica gel;

[0053] S103, coating the OCA optical adhesive on the surface of the optical grade PET film layer after electrostatic treatment, and curing it with UV light for 30 minutes to form an OCA optical adhesive layer, and finally attaching the PET light release film layer to the OCA optical adhesive layer to obtain an impact-resistant protective film, wherein the UV curing conditions are a wavelength of 360nm and an energy of 1500mj / cm 2 .

[0054] Example 4

[0055] The same as Example 3, except that an equal amount of 2-hydroxy-2-methyl-1-phenylpropanone is used instead of the photoinitiator, and the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5.

[0056] Example 5

[0057] The same as Example 3, except that an equal amount of ethyl 2,4,6-trimethylbenzoylphenylphosphonate is used instead of the photoinitiator, and the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5.

[0058] Example 6

[0059] The same as Example 3, except that an equal amount of 4-methoxyacetophenone is used instead of the photoinitiator, and the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5.

[0060] Example 7

[0061] The same as Example 3, except that an equal amount of triphenyl glycidyl ether methane is used instead of the cross-linking agent, and the cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2.

[0062] Example 8

[0063] The same as Example 3, except that an equal amount of vinyl cyclohexene diepoxide is used instead of the cross-linking agent, and the cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2.

[0064] Comparative Example 1

[0065] The same as Example 3, except that an equal amount of nano-silica with an average particle size of 30 nm is used to replace the modified silica prepared in Preparation Example 1.

[0066] Performance Testing

[0067] The anti-impact protective films prepared in Examples 1 to 8 and Comparative Example 1 were sampled, and after peeling off the PET light release film layer and the PET heavy release film (i.e., the actual use layer, including the OCA optical adhesive layer, the optical grade PET film layer and the silicone layer), the silicone layer was adhered to a high-transparency glass and tested. The test results are shown in Table 1.

[0068] Light transmittance test: Tested in accordance with JIS K736 standard;

[0069] Haze test: Tested in accordance with JIS K736 standard;

[0070] Hardness test: A pencil with a weight of 1kg is placed at a 45° angle to the contact surface of the test object. Five consecutive scratches with a length of 5-7mm are made using a pencil (Mitsubishi 7H pencil) scratch tester. A 10x magnifying glass is used to observe whether there are scratches on the surface.

[0071] Impact test: At a distance of two meters, use a 130-gram steel ball to impact the sample to be tested, and observe whether the glass of the sample to be tested has cracks or breaks;

[0072] Silicone layer peeling force test: According to JISZ0237 standard, the test was carried out at 300mm / min and 180°.

[0073] Table 1 Performance test

[0074]

[0075] Analyzing the data in Table 1, we can see that:

[0076] 1) The light transmittance of the anti-impact protective film obtained in Examples 1 to 3 is ≥ 95.1%; the haze is between 0.2-0.3%, the hardness is relatively hard, and it will not be scratched; it has excellent anti-impact performance and will not be easily damaged by impact.

[0077] 2) A comparative analysis of the performance of the anti-impact protective films prepared in Example 3 and Example 4-Example 6 was conducted, and a photoinitiator consisting of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5 was used, and the synergistic effect between them was utilized to improve the reaction rate and cross-linking effect of the OCA optical adhesive layer, improve the tensile strength and flexibility of the OCA optical adhesive layer, and further enhance the impact resistance of the entire anti-impact protective film.

[0078] 3) A comparative analysis of the performance of the anti-impact protective film prepared in combination with Example 3 and Example 7-Example 8 is conducted. The cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:2. By utilizing the synergistic effect therebetween, the cross-linking performance and impact resistance of the OCA optical adhesive layer can be effectively enhanced, the flexibility of the adhesive layer can be improved, and the impact resistance of the entire anti-impact protective film can be thereby improved.

[0079] 4) In combination with the comparative analysis of the performance of the anti-impact protective film prepared in Example 3 and Comparative Example 1, the modified silica prepared in Preparation Example 1 is used to react the nano-silica modified with γ-aminopropyltriethoxysilane with 2,6-di-tert-butylphenol to form modified silica. This modified silica can enhance the lipophilicity and functionality of the nano-silica, improve the interface performance with the OCA optical adhesive, and further enhance the impact resistance of the protective film. The addition of modified silica can enhance the interface performance of the OCA optical adhesive layer, improve the agglomeration of nano-silica, form physical cross-linking points with nano-silica as the core, and enhance the impact resistance of the OCA optical adhesive.

[0080] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. An anti-impact protective film, characterized in that: include: A PET light release film layer, an OCA optical adhesive layer, an optical-grade PET film layer, a silicone layer and a PET heavy release film, wherein the PET light release film layer, the OCA optical adhesive layer, the optical-grade PET film layer, the silicone layer and the PET heavy release film are sequentially bonded and connected from top to bottom, wherein the OCA optical adhesive layer comprises the following preparation raw materials by mass: 20-25 parts of n-propyl acrylate, 25-30 parts of isobornyl methacrylate, 2-4 parts of hydroxyethyl acrylate, 30-35 parts of diluent, 2-3 parts of glycidyl acrylate, 5-7 parts of modified silica, 0.5-1 parts of photoinitiator, 0.5-1 parts of cross-linking agent and 0.8-1.2 parts of antioxidant; the thickness of the OCA optical adhesive layer is 190-210 μm; The preparation method of the modified silicon dioxide comprises the following steps: S41, ultrasonically dispersing 10 g of nano-silica in an ethanol aqueous solution of 50 g of ethanol and 10 g of water, adding 4 g of γ-aminopropyltriethoxysilane, setting the system temperature to 75° C., stirring for 6-10 h, and after the reaction is completed, centrifuging the solid sample, washing, and drying to obtain γ-aminopropyltriethoxysilane-modified silica; S42, add the obtained γ-aminopropyltriethoxysilane modified silica to 30g of tetrahydrofuran, ultrasonically disperse, add 1.2g of 2,6-di-tert-butylphenol and 2.5g of potassium carbonate, mix well, raise the system temperature to 75°C, react for 7-12h, centrifuge the product to separate the solid sample, wash the solid sample with deionized water to neutrality, and finally vacuum dry to obtain modified silica, wherein the average particle size of the nano silica is 30nm; The photoinitiator is composed of 2-hydroxy-2-methyl-1-phenylpropanone, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 4-methoxyacetophenone in a mass ratio of 3:2:5; The cross-linking agent is composed of triphenyl glycidyl ether methane and vinyl cyclohexene diepoxide in a mass ratio of 5:

2.

2. The anti-impact protective film according to claim 1, characterized in that: The thickness of the PET light release film layer is 47-53 μm; the thickness of the PET heavy release film layer is 72-78 μm; the thickness of the optical-grade PET film layer is 72-78 μm, and its light transmittance is 98%.

3. The impact-resistant protective film according to claim 1, characterized in that: The thickness of the silicone layer is 42-48 μm; the peeling force of the silicone layer is ≤6 g / inch at 300 mm / min and 180° according to JIS Z0237 standard, and the adhesion between the silicone layer and the glass is 3-6 g / inch.

4. The impact-resistant protective film according to claim 1, characterized in that: The diluent is one of hydroxyethyl methacrylate, pentaerythritol rosin ester and isooctyl acrylate.

5. The impact-resistant protective film according to claim 1, characterized in that: The antioxidant is at least one of tert-butylhydroquinone, hexaethylphosphorotriamide and thiophosphoryl disulfide.

6. A method for preparing an anti-impact protective film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S101, stirring and mixing n-propyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, diluent, glycidyl acrylate, modified silica, photoinitiator, crosslinking agent and antioxidant to obtain OCA optical adhesive for standby use; S102, coating the surface of the optical-grade PET film layer with silica gel, and after heat curing, forming a silica gel layer, and then attaching the PET heavy release film light film layer to the silica gel layer, and performing electrostatic treatment on the side of the optical-grade PET film layer that is not coated with silica gel; S103, coating the OCA optical adhesive on the surface of the optical grade PET film layer after electrostatic treatment, and curing it with ultraviolet light for 25-35 minutes to form an OCA optical adhesive layer, and finally attaching the PET light release film layer to the OCA optical adhesive layer to obtain an impact-resistant protective film, wherein the ultraviolet curing conditions are a wavelength of 360nm and an energy of 1000-2000mj / cm 2 .